Characterization of two CD23 monoclonal antibodies with reactivity distinct from other antibodies within this cluster of differentiation. - Goff, L; Armitage, R; Beverley, P (1988)
We have produced two CD23 monoclonal antibodies (mAb), LA1 and LA2, which differ significantly in their patterns of reactivity compared to other mAb within this cluster. Unlike other CD23 mAb, LA1 and LA2 show virtually no reactivity with freshly isolated tonsil B lymphocytes or mantle zone lymphocytes in tissue section. That LA1 and LA2 are CD23 mAb is confirmed by their precipitation of a 45,000 MW surface protein from B cells and strong reactivity with a CD23 transfectant. Cross-blocking studies with four well-characterized CD23 mAb show that LA1 and LA2 recognize the same, distinct epitope of the CD23 molecule. However, similar to other CD23 mAb, expression of LA1 and LA2 increases after activation. Following removal of cells staining with the well-characterized CD23 mAb MHM6, using a highly efficient magnetic bead technique, LA1 and LA2, but not other CD23 mAb, react with a subpopulation of the remaining cells when activated with interleukin-4 (IL-4) or phorbol ester. Soluble LA1 and MHM6 both provide a co-stimulatory signal for phorbol ester-induced B-cell proliferation. This response is increased if these mAb are used to cross-link the CD23 molecule. Interestingly, despite the fact that LA2 and LA1 cross-block, LA2 has no effect on functional responses in its soluble form but can elicit a comparable increase in proliferation when cross-linked. Results presented here suggest that the novel CD23 mAb, LA1 and LA2, recognize a distinct form of the CD23 molecule, expressed only on activation. These mAb define a subpopulation of activated B cells which do not stain with other CD23 mAb.